How some Singapore small and medium enterprises are using the Internet. - Chong, Chee Weng. (2008)
The Internet is an international network of computers which is fast gaining popularity both as a commercial and communication tool. There are immense benefits that the Small and Medium Enterprises (SMEs) in Singapore can reap from the Internet. Our research seeks to find out how the SMEs in Singapore are using the Internet in their business operations. The Internet competence of the SMEs is evaluated based on their role as information users and information providers.